The Good-Subject Effect: Investigating Participant Demand Characteristics - Nichols, Austin Lee; Maner, Jon K. (The Journal of general psychology, 2008)
Although researchers are often concerned with the presence of participant demand, few have directly examined effects of demand on participant behavior. Before beginning the present study, a confederate informed participants (N = 100) of the study's purported hypothesis. Participants then performed a laboratory task designed to evaluate the extent to which they would respond in ways that may confirm or disconfirm the hypothesis of the study. The authors found that participants tended to respond in ways that confirmed the hypothesis, yet this tendency depended on attitudes toward the experiment or experimenter and other individual differences. In addition, results suggested that suspicion probes may be ineffective in measuring participants' previous knowledge and suspicion. Findings indicate the need for more research and consideration of demand in the design of studies and analysis of data.